Fiscal Federalism in Crisis: Lessons for Europe from the US - Zsolt Darvas (Hungarian Academy of Sciences, Institute of Economics, 2010)
The euro area is facing crisis, while the US is not, though the overall fiscal situation and outlook is better in the euro area than in the US, and though the US faces serious state-level fiscal crises. A higher level of fiscal federalism would strengthen the euro area, but is not inevitable. Current fiscal reform proposals (strengthening of current rules, more policy coordination and an emergency financing mechanism) will if implemented result in some improvements. But implementation might be deficient or lack credibility, and could lead to disputes and carry a significant political risk. Introduction of a Eurobond covering up to 60 percent of member states' GDP would bring about much greater levels of fiscal discipline than any other proposal, would create an attractive Eurobond market, and would deliver a strong message about the irreversible nature of European integration.
Keywords: E62; H12; H60; H77; 330; federalism; redistribution; stabilisation; risk-sharing; crisis; euro-area governance reform; Eurobond; Finanzbeziehungen; Eurozone; EU-Staaten; USA